INTEGRASI PENDIDIKAN KELUARGA DAN SEKOLAH BERBASIS NILAI BUDAYA LOKAL BAGI PENINGKATAN PRESTASI SISWA - Herdiansyah, Hendi (STKIP Pesisir Selatan, 2025)
This study aims to explore an integrative conceptual model between home and school education based on local values to improve student achievement. The research focuses on identifying and designing an integration model that not only connects the roles of families and schools but also accommodates the local values embedded in Indonesian society. This study employs an exploratory qualitative method, as it seeks to deeply investigate the concept of integration from various scientific literatures and to identify an appropriate conceptual model. Data collection techniques were carried out through library research by reviewing open-access scientific journals from the past ten years, books, research reports, and educational policy documents, followed by content analysis of literature relevant to the integration of family-school education and Indonesian local values. The findings highlight five main pillars in the collaborative integration model: shared goals, value alignment, functional programs, joint supervision, and joint assessment. This model offers novelty by emphasizing the role of local values as a binding element between families and schools, as well as a reinforcement of students' cultural identity. The study provides theoretical contributions to the development of educational policies and serves as a foundation for future empirical research to examine the effectiveness of implementing the model in various Indonesian school contexts.